Nursing education in the digital era: the role of digital competence in enhancing academic motivation and lifelong learning among nursing students - Shaimaa Mohamed Amin; Shimaa Abd El-fattah Mahgoub; Ahmed Farghaly Tawfik; Dalia E. Khalil; Ahmed Abdelwahab Ibrahim El-Sayed; Mohamed Hussein Ramadan Atta; Ali Albzia; Shadia Ramadan Morsy Mohamed (BMC Nursing)
Abstract Background Digital competence is increasingly crucial for academic success and lifelong learning, especially in health education fields such as nursing. However, limited research examines the relationship between digital competence, academic motivation, and lifelong learning among nursing students. Aim To assess the relationship between digital competence, academic motivation, and lifelong learning among undergraduate nursing students and explore the mediating role of academic motivation in this relationship. Methods A descriptive comparative cross-sectional study was conducted, guided by the STROBE guidelines. Using systematic random sampling, 500 undergraduate nursing students were selected from Mansoura University, Egypt. Data were collected from July to August 2024 using three validated scales: the Students’ Digital Competence Scale, the Lifelong Learning Scale, and the Academic Motivation Scale. Descriptive statistics, Pearson correlation, and multiple regression analysis were used to analyze the data. Results The results showed a strong positive correlation between digital competence and academic motivation (r = 0.53, p < 0.001), as well as between digital competence and lifelong learning (r = 0.61, p < 0.001). Students with higher digital competence scores also had significantly higher academic motivation (4.21 ± 0.45) and lifelong learning tendencies (4.37 ± 0.48). Multiple regression analysis confirmed that digital competence significantly predicted both academic motivation (β = 0.38, p < 0.001) and lifelong learning (β = 0.44, p < 0.001). Conclusion Digital competence significantly enhances academic motivation and promotes lifelong learning among nursing students. The findings emphasize the need for nursing curricula to integrate digital competence training to improve educational outcomes and prepare students for future challenges in healthcare. Clinical trial number Not applicable.